Method for preparing liquid metal composite film, composite film and application
Patent Information
- Application Number
- CN202610876075.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-17
- Publication Date
- 2026-09-11
AI Technical Summary
将液态金属引入弹性体基体中,有望赋予材料稳定的电学输出能力,但现有液态金属/弹性体复合方式通常存在界面稳定性差、制备工艺复杂、液态金属流动性难以控制、液态金属在大应变下泄漏或导电通路断裂等问题
[0017] The beneficial effects of the technical solution provided by the embodiments of the present invention are as follows: The present invention introduces liquid metal particles into the cholesteric phase liquid crystal elastomer precursor system, and utilizes the density difference between the liquid metal particles and the liquid crystal precursor system to induce the liquid metal particles to spontaneously settle along the film thickness direction during solvent evaporation, self-assembly, and cross-linking reactions, forming a layered structure with a sparse upper layer and a rich lower layer. This layered structure is not a simple uniform filler dispersion structure, but rather forms structural color response regions and conductive functional regions in the same film, thereby achieving spatial division of optical and electrical functions.
Smart Images

Figure CN122726475A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional composite materials technology, and specifically relates to a method for preparing liquid metal composite films, the composite films, and their applications. Background Technology
[0002] With the development of technologies such as flexible electronics, smart wearables, human-computer interaction, and soft robotics, flexible smart materials capable of simultaneously sensing external stimuli, providing visual feedback, and outputting electrical signals have attracted widespread attention. Biological skin can sense external stimuli such as pressure, temperature, and deformation, and achieve environmental adaptation and information feedback through multi-signal coordination. Creatures like octopuses and chameleons can also express dynamic information through changes in skin color. Therefore, constructing skin-like flexible materials that combine structural color response and electrical response capabilities has become an important research direction in the fields of flexible sensors and biomimetic electronic skin.
[0003] Cholesteric liquid crystal elastomers (LCEs) are a class of liquid crystal elastomer materials with a periodic helical arrangement structure. They can selectively reflect circularly polarized light of specific wavelengths and exhibit structural color characteristics. When CEEs are subjected to external stimuli such as stretching, pressing, or temperature changes, the pitch of their helical structure changes, causing a shift in the reflected wavelength and achieving a visual response. However, traditional CEEs primarily exhibit optical and mechanical responses, with relatively limited electrical properties, making it difficult to meet the requirements of intelligent sensing systems for multi-signal coupling, electrical quantization detection, and real-time signal acquisition.
[0004] In existing technologies, some studies attempt to combine photonic structures with ionic conductive systems or electronic conductive networks to obtain a synergistic response of optical and electrical signals. However, ionic conductive materials typically suffer from limited conductivity, restricted response frequency, and insufficient environmental stability. Furthermore, the addition of ordinary solid conductive fillers can easily reduce the stretchability of flexible matrices and may disrupt the helical ordered structure and structural color output effect of cholesteric liquid crystal elastomers.
[0005] Liquid metals possess high conductivity, fluidity, and deformation adaptability, making them promising candidates for application in flexible conductive materials. Introducing liquid metals into elastomer matrices is expected to endow materials with stable electrical output capabilities. However, existing liquid metal / elastomer composite methods typically suffer from problems such as poor interfacial stability, complex fabrication processes, difficulty in controlling the fluidity of liquid metals, and leakage or breakage of conductive pathways under large strains. Summary of the Invention
[0006] The purpose of this invention is to provide a composite thin film that combines the structural color response of the cholesteric phase with the conductivity of liquid metal and its preparation method.
[0007] This invention is achieved through the following measures: a method for preparing a liquid metal composite thin film, characterized by comprising the following steps: S1. Liquid metal is added to a dispersion medium and ultrasonically dispersed to obtain a liquid metal suspension. The liquid metal suspension is centrifuged to obtain liquid metal particle precipitate. The liquid metal particle precipitate is added to deionized water for treatment to obtain liquid metal particles. S2. Dissolve liquid crystal monomers and chiral liquid crystal molecules in a solvent to form a liquid crystal mixed solution. Then add a catalyst, chain extender, crosslinking agent and photoinitiator to the liquid crystal mixed solution and mix them to obtain a liquid crystal precursor solution for forming a cholesteric phase liquid crystal elastomer matrix. S3. Add liquid metal particles to the liquid crystal precursor solution and disperse them to obtain a composite precursor solution containing liquid metal particles; S4. The composite precursor solution is placed in a film-forming mold and allowed to stand to allow the solvent to evaporate. During the solvent evaporation process, liquid crystal molecules are induced to self-assemble to form a cholesteric helical ordered structure and undergo Michael addition cross-linking. At the same time, liquid metal particles spontaneously settle in the composite precursor solution along the thickness direction to form a layered structure. The bottom region of the layered structure has a dense distribution of liquid metal particles, while the upper region has a relatively sparse distribution of liquid metal particles. S5. Photocuring the layered structure yields a liquid metal composite film based on cholesteric liquid crystal elastomer. In this process, the relatively sparse distribution of liquid metal particles corresponds to the formation of structural color response regions, while the dense distribution of liquid metal particles corresponds to the formation of conductive functional regions, enabling the liquid metal composite film based on cholesteric liquid crystal elastomer to generate structural color changes and electrical signal outputs under the action of external force.
[0008] Further, in step S1, the dispersion medium is anhydrous ethanol, and the liquid metal is a gallium-indium alloy; The liquid metal particles were treated by adding them to deionized water, including adding the liquid metal particles to deionized water and dispersing them by vortexing, followed by rapid freezing with liquid nitrogen and vacuum freeze-drying to obtain liquid metal particles.
[0009] Further, in step S2, the solvent is toluene, the liquid crystal monomer and the chiral liquid crystal molecule are dissolved in the toluene under heating conditions, and the catalyst, the chain extender, the thiol crosslinking agent and the photoinitiator are added after cooling.
[0010] Further, in step S2, the liquid crystal monomer is RM257, the chiral liquid crystal molecule is LC756, the catalyst is DPA, the chain extender is EDDET, the thiol crosslinking agent is PETMP, and the photoinitiator is I-651.
[0011] Furthermore, the particle size of the liquid metal particles ranges from 100 nm to 2 μm.
[0012] Furthermore, the amount of liquid metal particles added to the composite precursor solution is from 35 wt.% to 60 wt.%.
[0013] Furthermore, the liquid metal particles have a particle size of 300 nm to 400 nm, and the amount of liquid metal particles added to the composite precursor solution is 40 wt.%.
[0014] Furthermore, the molar ratio of the liquid crystal monomer RM257, the chain extender EDDET, and the thiol crosslinking agent PETMP is 1.06:0.08:0.85, and the amount of photoinitiator I-651 added is 1 wt.%.
[0015] The present invention also provides a liquid metal composite thin film, characterized in that it is prepared by the aforementioned preparation method.
[0016] The present invention also provides a triboelectric nanogenerator, characterized in that it includes an upper electrode and a lower electrode, wherein the upper electrode includes a conductive tape and a polymer triboelectric film disposed on one side of the conductive tape, and the lower electrode is a liquid metal composite film based on cholesteric phase liquid crystal elastomer prepared by the preparation method. The sparse region of the liquid metal particles faces the polymer friction film and serves as the friction contact area, while the rich region of the liquid metal particles serves as the conductive electrode area, enabling the contact-separation triboelectric nanogenerator to output a voltage signal during the contact-separation process.
[0017] The beneficial effects of the technical solution provided by the embodiments of the present invention are as follows: The present invention introduces liquid metal particles into the cholesteric phase liquid crystal elastomer precursor system, and utilizes the density difference between the liquid metal particles and the liquid crystal precursor system to induce the liquid metal particles to spontaneously settle along the film thickness direction during solvent evaporation, self-assembly, and cross-linking reactions, forming a layered structure with a sparse upper layer and a rich lower layer. This layered structure is not a simple uniform filler dispersion structure, but rather forms structural color response regions and conductive functional regions in the same film, thereby achieving spatial division of optical and electrical functions.
[0018] In this invention, the sparse regions of liquid metal particles can enhance structural color output by utilizing the light reflection and scattering effects of the liquid metal particles while maintaining the integrity of the cholesteric helical ordered structure; the regions rich in liquid metal particles can form stable conductive pathways after mechanical sintering, enabling the composite film to output electrical signals. Therefore, the composite film can simultaneously possess both structural color visualization response and electrical quantification detection capabilities, improving the information expression dimension and detection reliability of flexible sensing materials.
[0019] This invention allows for the adjustment of the structural color, electrical conductivity, and response characteristics of composite films by controlling the particle size, amount of liquid metal particles, and content of chiral liquid crystal molecules. Specifically, the introduction of an appropriate amount of liquid metal particles can improve the structural color saturation without significantly disrupting the cholesteric helical structure, and form a conductive pathway after mechanical sintering, thereby achieving synergistic optimization of structural color and electrical properties.
[0020] The composite film prepared by this invention can generate structural color changes and resistance signal changes under stretching, pressing, or bending, and can be used for photoelectric dual-modal sensing of strain, pressure, and human joint movement. Compared with single optical sensing or single resistance sensing, this invention can achieve intuitive positioning and visual feedback through structural color changes, and achieve quantitative acquisition and real-time monitoring through electrical signal output. It is suitable for flexible electronic skin, intelligent wearable systems, human-computer interaction devices, and soft robots.
[0021] This invention can also utilize the layered structure of the composite film itself to construct a contact-separation triboelectric nanogenerator, where the sparse regions of the liquid metal particles serve as the triboelectric contact regions, and the concentrated regions of the liquid metal particles serve as the conductive electrode regions. This structure can output a voltage signal during the contact-separation process and can generate different responses according to changes in the contact material, contact frequency, and pressure, thereby expanding the application of composite films in self-driven sensing and energy conversion. Attached Figure Description
[0022] To more clearly illustrate the technical solution of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. Obviously, the drawings listed below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0023] Figure 1 This is a flowchart of a method for preparing a liquid metal composite thin film according to an embodiment of the present invention; Figure 2 This is a schematic diagram illustrating the preparation of a liquid metal composite film based on a cholesteric phase liquid crystal elastomer in an embodiment of the present invention; Figure 3 This is the infrared spectrum of the CLCE precursor solution and the CLCE-LM composite film in the embodiments of the present invention; Figure 4 In the image, a is a sample photograph of the CLCE and CLCE-LM composite thin film; b is the reflectance spectrum of the two thin films; c is the CIE chromaticity diagram of the two thin films. Figure 5 These are photographs of CLCE-LM composite film samples from embodiments of the present invention (LM content: 35wt.%, 40wt.%, 50wt.%, 60wt.%). Figure 6 In the diagram, 'a' represents the reflectance spectrum of CLCE-LM composite films with different LM contents; 'b' represents the corresponding CIE chromaticity diagram. Figure 7 The images show SEM images and particle size statistics of LM particles after ultrasonic treatment for different times, where a represents 3 min; b represents 5 min; c represents 10 min; d represents 15 min; e represents 30 min; and f represents the change curve of LM particle size with ultrasonic time. Figure 8 In the figure, a represents the reflectance spectrum of CLCE-LM composite films with different LM particle sizes at a 40wt.% LM particle addition level; b represents the CIE colorimetric diagram. Figure 9 In the figure, a represents the electrical properties of CLCE-LM composite films with different LM contents; b represents a comparison of the bottom surface of the film with 40 wt.% LM content before and after sintering. Figure 10 In the diagram, 'a' represents the reflectance spectrum of CLCE composite films with different fillers; 'b' represents their CIE chromaticity diagram. Figure 11 Cross-sectional SEM images of the CLCE-LM composite thin film and its elemental distribution of Ga, In, and C; Figure 12 Images of the green CLCE-LM composite film under natural light and left / right circularly polarized light under vertical observation. Figure 13 To observe the color change of the CLCE-LM composite film at angles of 90°, 80°, 70°, 60°, 50°, 40° and 30° to the horizontal plane; Figure 14 In the figures, a is a photograph of CLCE-LM composite film samples with different LC756 addition amounts (4%, 4.5%, 5%, 5.5%, 6%, 6.5%); b is the corresponding reflectance spectrum; c is the CIE colorimetric diagram. Figure 15 The DSC curves of the CLCE-LM composite film and the structural color changes at the phase transition temperature are shown. Figure 16 In the figure, a is the stress-strain curve of the CLCE film and the CLCE-LM composite film; b is the tensile curve of the CLCE-LM composite film under 40% strain after 100 cycles. Figure 17 In the figure, 'a' represents the structural color change of the CLCE-LM composite film under different tensile strains; 'b' represents the corresponding reflection spectrum. Figure 18 The structural color change of the initially red CLCE-LM composite film at 40 kPa, 80 kPa, and 160 kPa; Figure 19The change rate of resistivity of CLCE-LM thin film as a function of tensile strain; Figure 20 In this context, 'a' represents the rate of change of resistivity of the CLCE-LM composite film under different tensile strains; 'b' represents the tensile stability of the film after 100 cycles at 20% strain. Figure 21 In this context, 'a' represents the change rate of resistance of the CLCE-LM composite film as a function of the finger bending angle; 'b' represents the rate of resistance change response at different angles during the finger bending cycle. Figure 22 A schematic diagram illustrating the working principle of a triboelectric nanogenerator assembled from CLCE-LM composite thin films; Figure 23 Dielectric properties of CLCE and CLCE-LM composite films; Figure 24 The TENG output voltage signal is used for PTFE (a) and PE (b) as the top contact layer; Figure 25 The output voltage signal of TENG at different contact frequencies is obtained by using PTFE as the upper contact layer. Figure 26 The voltage signal output by the CLCE-LM composite film when the finger presses the film periodically at different intensities. Detailed Implementation
[0024] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. Of course, the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0025] In this specification, liquid metal can be abbreviated as LM, cholesteric liquid crystal elastomer can be abbreviated as CLCE, liquid metal composite film based on cholesteric liquid crystal elastomer can be abbreviated as CLCE-LM composite film, and triboelectric nanogenerator can be abbreviated as TENG.
[0026] Example 1: See Figure 1 and Figure 2 This embodiment provides a method for preparing a liquid metal composite thin film, characterized by the following steps: S1. Liquid metal is added to a dispersion medium and ultrasonically dispersed to obtain a liquid metal suspension. The liquid metal suspension is centrifuged to obtain liquid metal particle precipitate. The liquid metal particle precipitate is added to deionized water for treatment to obtain liquid metal particles. In step S1, the dispersion medium is anhydrous ethanol, and the liquid metal is a gallium-indium alloy. The liquid metal particles are precipitated and treated by adding them to deionized water, including adding the liquid metal particles precipitated to deionized water and dispersing them by vortexing, followed by rapid freezing with liquid nitrogen and vacuum freeze-drying to obtain liquid metal particles.
[0027] Specifically, in this embodiment, the liquid metal is a eutectic gallium-indium alloy, in which the gallium content is 75% and the indium content is 25%. The eutectic gallium-indium alloy is liquid at room temperature and has high conductivity and deformation adaptability. When it is introduced into the cholesteric liquid crystal elastomer matrix as a conductive functional component, it can provide an electrical output basis for the composite film.
[0028] First, liquid metal particles are prepared. 0.5 g of eutectic gallium-indium alloy liquid metal is weighed and added to 12 mL of anhydrous ethanol. The mixture is then ultrasonically dispersed using an ultrasonic cell disruptor, causing the liquid metal droplets to break up and disperse in the anhydrous ethanol under ultrasonic cavitation, resulting in a liquid metal suspension. The particle size of the liquid metal particles is controlled by adjusting the ultrasonic power and ultrasonic time. In one specific embodiment, the ultrasonic power is fixed at 40%, and the ultrasonic time is selected as 3 min, 5 min, 10 min, 15 min, or 30 min, corresponding to liquid metal particles with average particle sizes of approximately 2.83 μm, 1.12 μm, 364 nm, 315 nm, or 164 nm.
[0029] The prepared liquid metal suspension was placed in a centrifuge and centrifuged at 3000 mL / min. The mixture was centrifuged for 5 minutes under the specified conditions to obtain a precipitate of liquid metal particles. After removing the supernatant, deionized water was added to the precipitate, and the mixture was thoroughly mixed and dispersed under vortexing. The dispersion containing the liquid metal particles was then rapidly frozen in liquid nitrogen and freeze-dried in a vacuum freeze dryer to obtain the liquid metal particles. The particle size of the liquid metal particles was 100 nm to 2 μm. In this embodiment, liquid metal particles with a particle size of 300 nm to 400 nm were preferably used, and more preferably, liquid metal particles with a particle size of approximately 315 nm were used.
[0030] S2. Dissolve liquid crystal monomers and chiral liquid crystal molecules in a solvent to form a liquid crystal mixed solution. Then add a catalyst, chain extender, crosslinking agent and photoinitiator to the liquid crystal mixed solution and mix them to obtain a liquid crystal precursor solution for forming a cholesteric phase liquid crystal elastomer matrix. In step S2, the solvent is toluene. The liquid crystal monomer and the chiral liquid crystal molecule are dissolved in the toluene under heating conditions. After cooling, the catalyst, the chain extender, the thiol crosslinking agent and the photoinitiator are added.
[0031] Specifically, in this embodiment, 226 mg of liquid crystal monomer RM257 was weighed and a certain mass fraction of chiral liquid crystal molecule LC756 was added. The two were dissolved in 140 mg of toluene and stirred at 80°C until a homogeneous liquid crystal mixture was formed. The liquid crystal mixture was then cooled to room temperature, and 60 mg of catalyst DPA solution, 56 mg of chain extender EDDET, 15 mg of thiol crosslinking agent PETMP, and photoinitiator I-651 were added sequentially. The mixture was stirred thoroughly to ensure uniform mixing of all components, yielding the liquid crystal precursor solution. The mass ratio of toluene to DPA in the catalyst DPA solution was 20:1, the molar ratio of liquid crystal monomer RM257, chain extender EDDET, and thiol crosslinking agent PETMP was 1.06:0.08:0.85, and the amount of photoinitiator I-651 added was 1 wt.%. S3. Add liquid metal particles to the liquid crystal precursor solution and disperse them to obtain a composite precursor solution containing liquid metal particles; Specifically, pre-prepared liquid metal particles are added to the liquid crystal precursor solution and stirred and dispersed to obtain a composite precursor solution containing liquid metal particles. The amount of liquid metal particles added can be 25 wt.%, 30 wt.%, 35 wt.%, 40 wt.%, 45 wt.%, 50 wt.%, or 60 wt.%. When the amount of liquid metal particles added is low, it is difficult to form a continuous conductive path inside the composite film. When the amount of liquid metal particles added is too high, the liquid metal particles interfere with the continuity of the cholesteric phase helical ordered structure and may lead to an increase in the surface roughness of the composite film. Therefore, in this embodiment, the amount of liquid metal particles added is preferably 35 wt.% to 45 wt.%, more preferably 40 wt.%.
[0032] S4. The composite precursor solution is placed in a film-forming mold and allowed to stand to allow the solvent to evaporate. During the solvent evaporation process, liquid crystal molecules are induced to self-assemble to form a cholesteric helical ordered structure and undergo Michael addition cross-linking. At the same time, liquid metal particles spontaneously settle in the composite precursor solution along the thickness direction to form a layered structure. The bottom region of the layered structure has a dense distribution of liquid metal particles, while the upper region has a relatively sparse distribution of liquid metal particles. Specifically, the composite precursor solution containing liquid metal particles was transferred to a 25mm × 15mm film-forming mold and allowed to stand at room temperature for 24 hours. During the standing process, toluene slowly evaporated and induced the liquid crystal molecules to self-assemble into an ordered cholesteric helical structure; simultaneously, the system underwent a Michael addition reaction and gradually formed a cross-linked network. Because the density of the liquid metal particles was greater than that of the liquid crystal precursor system, the liquid metal particles spontaneously settled along the thickness direction of the composite precursor solution before the cross-linked network was completely solidified, gradually accumulating towards the side closer to the bottom of the film-forming mold; as the cross-linked network gradually formed and solidified, the settling state of the liquid metal particles was fixed, forming a layered structure; wherein, the liquid metal particles were densely distributed in the bottom region of the layered structure, and relatively sparsely distributed in the upper region.
[0033] S5. Photocuring the layered structure yields a liquid metal composite film based on cholesteric liquid crystal elastomer. Specifically, the resulting layered structure was cured under ultraviolet light. The power density of the ultraviolet light was 180 m³ / s. The irradiation time was 15 min; after UV curing, the residual double bonds underwent further free radical polymerization, which further stabilized the crosslinked network in the composite film, resulting in a liquid metal composite film based on cholesteric liquid crystal elastomer. By adjusting the content of chiral liquid crystal molecules LC756 and the amount of liquid metal particles added, liquid metal composite films based on cholesteric liquid crystal elastomer with different reflection wavelengths and different conductivity properties can be obtained.
[0034] In this process, the relatively sparse distribution of liquid metal particles corresponds to the formation of structural color response regions, while the dense distribution of liquid metal particles corresponds to the formation of conductive functional regions, enabling the liquid metal composite film based on cholesteric liquid crystal elastomer to generate structural color changes and electrical signal outputs under the action of external force.
[0035] Example 2: Based on Example 1, in order to verify the polymerization of liquid crystal monomers and the formation of cross-linked networks, infrared spectroscopy tests can be performed on the CLCE precursor solution and the CLCE-LM composite film (the test results can be found in...). Figure 3 ). CLCE precursor solution at 3100 1680 and 2600 Characteristic absorption peaks for =C–H, C=C, and S–H were observed at the points, indicating the simultaneous presence of acrylate and thiol active groups in the system. After room temperature polymerization and UV curing, the characteristic absorption peaks in the infrared spectrum of the CLCE-LM composite film disappeared, proving that the double bonds and thiol groups in the system had fully participated in the reaction. This indicates that the liquid crystal monomer underwent a Michael addition reaction with the chain extender and crosslinking agent, and the residual double bonds further underwent free radical polymerization under the action of the photoinitiator, forming a crosslinked network structure.
[0036] To illustrate the enhancing effect of liquid metal particles on the structural color of cholesteric liquid crystal elastomers, pure CLCE red films and CLCE-LM red composite films with an LM addition of 40 wt.% were prepared under the same conditions (e.g., [missing information]). Figure 4 (a) Compared to the CLCE film, the addition of LM particles significantly enhances the structural color of the CLCE-LM film. This is likely due to the excellent light reflection capability of the LM particles, which, dispersed within the CLCE matrix, act as a "reflective substrate" or "optical backplane" to some extent. When incident light passes through the CLCE spiral structure and undergoes selective reflection, the unreflected portion of the light can undergo secondary reflection on the surface of the LM particles, participating again in the Bragg reflection process and enhancing the saturation of the structural color.
[0037] Perform visible light reflectance spectroscopy testing on it (e.g.) Figure 4 (b) The color saturation of the thin film is evaluated by comparing the full width at half maximum (FWHM) of the reflection peak. A narrower FWHM indicates a concentrated reflection band and higher structural color saturation, while an increased FWHM indicates a wider pitch distribution and lower color saturation. It can be seen that the addition of LM particles significantly reduces the FWHM of the reflection peak in the red film of the pure cholesteric liquid crystal elastomer and significantly improves the structural color saturation. This is converted into a CIE chromaticity diagram (e.g., ...). Figure 4 As can be seen from c), after adding LM particles, the chromaticity points of the film shift towards higher saturation, indicating that the addition of LM particles has an enhancing effect on the saturation of the structural color of the CLCE film.
[0038] To illustrate the effect of LM particle addition on the structural color of CLCE-LM composite films, under the same conditions, CLCE-LM composite films with LM particle additions of 35 wt.%, 40 wt.%, 50 wt.%, and 60 wt.% were prepared with LC756 addition at 4.5 wt.%. Figure 5 As the LM particle content increases, the film color becomes more vibrant, and the saturation gradually improves. When the LM particle content increases to 60 wt.%, the excessive LM particle content affects the continuity and order of the spiral structure in CLCE, resulting in a significant increase in film surface roughness and a decrease in structural color saturation.
[0039] The effect of different LM particle contents on the structural color of CLCE-LM composite films was quantitatively analyzed, and reflectance spectra of the above samples were tested. Figure 6 (a) In the diagram, each sample exhibits a distinct cholesteric-selective reflectance peak in the visible light range. This is then converted into a CIE chromaticity diagram (…). Figure 6 (b) allows for a more intuitive comparison of the structural color saturation of different samples. As the content of LM particles increases, the saturation of the structural color of the CLCE-LM composite film first increases and then decreases. When the amount of LM particles added is 40 wt.%, the film has a high color saturation, indicating that the introduction of an appropriate amount of LM particles can enhance the structural color saturation without destroying the cholesteric phase structure.
[0040] To illustrate the effect of LM particle size on the structural color of the CLCE-LM composite film, the LM particle size is related to the ultrasonic dispersion power and time. With the ultrasonic power fixed at 40%, LM particles of different sizes were prepared by adjusting the ultrasonic time. 0.5 g of gallium-indium liquid metal droplets were ultrasonically treated in 12 mL of anhydrous ethanol for 3 min, 5 min, 10 min, 15 min, and 30 min, respectively. After centrifugation to remove the supernatant, the mixture was mixed with deionized water, and then frozen in liquid nitrogen and freeze-dried to obtain LM particles of different sizes. SEM measurements were performed (e.g., ...). Figure 7 LM particles are relatively uniformly distributed spherical particles, and their particle size is statistically analyzed. Figure 7 The particle sizes of LM particles with different ultrasonic treatment times were 2.83 μm, 1.12 μm, 364 nm, 315 nm, and 164 nm, respectively. The relationship between the particle size of LM particles and ultrasonic treatment time is as follows: Figure 7 As the ultrasonic time increases, within 0-10 min, LM droplets undergo violent breakup under the cavitation effect, and the particle size decreases rapidly; after 10 min, the difficulty of breaking up small particles increases, the particle size enters a slow refinement stage, and the system gradually tends to stabilize.
[0041] Furthermore, under the conditions of LC756 addition of 4.5 wt.%, LM particle addition of 40 wt.%, and other component ratios remaining unchanged, CLCE-LM composite films with different LM particle sizes were prepared, and their reflectance spectra were tested. Figure 8 (a) In this diagram, the maximum reflected wavelength of all samples is between 590 and 650 nm, appearing macroscopically as red. This indicates that under the same chiral molecule addition, the pitch distribution of the system remains essentially consistent, and the change in LM particle size does not significantly alter the reflected wavelength of CLCE. This is then converted into a chromaticity diagram (…). Figure 8In section b), as the particle size of LM particles decreases, the color saturation of the CLCE-LM composite film first increases and then decreases. When the particle size decreases from 2.83 μm to 315 nm, the structural color saturation of the film gradually increases. This may be because the smaller particle size of the LM particles reduces the particle scattering intensity and makes the dispersion more uniform, which is conducive to forming a relatively uniform optical background and improving the monochromaticity of selective reflection. As the particle size of LM particles decreases to 165 nm, the structural color saturation of the film decreases. This may be because the particle size of LM particles is too small, making it difficult to settle during polymerization. A large amount of these particles accumulates in the upper layer, affecting the formation of the cholesteric helical structure and thus reducing the structural color saturation. Finally, an ultrasonic treatment time of 10 min was selected for the LM particles, resulting in a particle size of approximately 315 nm.
[0042] To illustrate the effect of liquid metal particle addition on the electrical properties of composite films, CLCE-LM composite films with LM particle addition amounts of 25 wt.%, 30 wt.%, 35 wt.%, 40 wt.%, and 45 wt.% were prepared under the condition that the LC756 addition amount was 4.5 wt.%, the LM particle size was approximately 315 nm, and the proportions of other components remained unchanged. The conductivity was then measured after mechanical sintering. Figure 9 (a) When the amount of LM particles added is less than 35 wt.%, the film is almost non-conductive, and the LM particles do not form a continuous conductive path inside the film. When the amount added increases to 40 wt.%, the film conductivity increases rapidly, reaching approximately 118. LM particles form a continuous conductive path inside the film. A comparison of the film's bottom surface before and after mechanical sintering (e.g.) Figure 9 As shown in b), the bottom surface of the unsintered film is dark gray, but after mechanical sintering, it exhibits a metallic luster. Further increasing the LM particle addition to 45 wt.% did not significantly increase the film conductivity. Considering both the structural color enhancement effect and the film's electrical properties, a further LM particle addition of 40 wt.% was selected.
[0043] To illustrate the advantage of liquid metal particles over other fillers in enhancing structural color, a 40 wt.% addition of LM particles was converted to a volume fraction of approximately 2.4 vol.%, and composite films of silica, graphite powder, carbon black, LM particles, and CLCE were prepared with the same volume fraction addition. Reflectance spectroscopy was then performed on these films. Figure 10 (a) Compared with other filler samples, the CLCE-LM composite film has a smaller half-width, indicating higher structural color saturation. This was converted into a CIE chromaticity diagram (…). Figure 10(b) In this context, the addition of all fillers shifts the chromaticity point towards the high saturation region, with CLCE-LM showing the largest shift and the most significant improvement in structural color saturation. This may be due to the enhanced light scattering and reflection effect formed by an appropriate amount of LM particles within the film, providing a "reflective substrate" or multiple scattering paths for the cholesteric phase structure, thereby improving the monochromaticity of the CLCE structural color.
[0044] To characterize the layered structure of the CLCE-LM composite film, based on the aforementioned comprehensive optimization of structural color and electrical properties, subsequent experiments used LM particles with a particle size of approximately 315 nm and an addition amount of 40 wt.% to prepare the CLCE-LM composite film. SEM measurements and elemental analysis were performed on the film cross-section. Figure 11 The LM particles exhibit a gradient distribution along the film thickness, with a denser distribution in the bottom region and a relatively sparser distribution in the upper region. This is mainly because the density of LM particles is higher than that of the CLCE precursor solution. During solvent evaporation and crosslinking reactions, the LM particles spontaneously settle under gravity and gradually accumulate at the bottom. As the network structure gradually forms and solidifies, the settled state is frozen, forming a layered structure.
[0045] This layered structure, induced by physical sedimentation, does not disrupt the formation of the cholesteric helical structure and achieves spatial separation between the optical and conductive functional layers. The low content of LM particles in the upper layer of the CLCE-LM composite film enhances structural color saturation while maintaining the integrity of the cholesteric structure; the high content of LM particles in the bottom layer, after mechanical sintering, more easily forms continuous conductive pathways, endowing it with electrical properties. The CLCE-LM composite film forms a layered composite structure in the thickness direction that combines structural color display and electrical output functions, laying the structural foundation for its multimodal sensing applications.
[0046] To verify the formation and chiral characteristics of the cholesteric helical structure in the CLCE-LM composite film, a CLCE-LM composite film with an LC756 content of 5% was prepared. Figure 12 When observed vertically under natural light, the film appears green. Covering the film surface with a left-handed polarizer causes the structural color to disappear, resulting in an overall gray appearance. When observed under a right-handed polarizer, the film's color recovers, matching its color under natural light. This indicates that the prepared CLCE-LM composite film selectively reflects right-handed circularly polarized light but does not reflect left-handed circularly polarized light. According to Bragg's principle of selective reflection, a helical structure only strongly reflects circularly polarized light with the same direction of rotation as the helix, indicating the formation of a chiral helical structure in the CLCE-LM composite film, with the helix direction being right-handed.
[0047] To illustrate the effect of observation angle on the optical response of composite thin films, a CLCE-LM composite thin film with 4% LC756 was prepared. Under the same incident light conditions, its structural color was characterized by changing the observation angle. Figure 13 When the observation direction is perpendicular to the film surface, the film appears red. As the observation direction gradually deviates from the normal direction (i.e., the angle with the horizontal plane gradually decreases), the film color continuously changes from red to green, exhibiting a significant blue shift. This is because the selective reflection of CLCE exhibits angle dependence; its reflection center wavelength satisfies Bragg's law of reflection. When the observation angle deviates from the normal direction, the effective reflection path changes, and the reflection center wavelength shifts towards shorter wavelengths, macroscopically manifesting as a continuous change from red to green. This demonstrates the successful preparation of a cholesteric helical structure with uniform orientation, complete structure, and stable and predictable optical response at different observation angles.
[0048] To illustrate the effect of the amount of chiral liquid crystal molecule LC756 added on the structural color regulation of CLCE-LM composite films, composite films with LC756 mass fractions of 4%, 4.5%, 5%, 5.5%, 6%, and 6.5% were prepared, respectively. Figure 14 (a) As the amount of LC756 added increases, when observed vertically under natural light, the structural color of the thin film gradually shifts from red to blue to purple, exhibiting a continuously tunable color change, effectively controlling the optical response of the CLCE-LM composite thin film.
[0049] Through the reflection spectrum of the thin film ( Figure 14 As shown in b), with the increase of LC756 content, the position of the reflection peak generally shifts towards shorter wavelengths. This is because the increase in chiral monomer content reduces the pitch P of the helical structure. According to Bragg's law of reflection, the reflection peak shifts towards shorter wavelengths, resulting in a significant blue shift, consistent with the macroscopic color change pattern. This can be converted into a CIE chromaticity diagram (…). Figure 14 (c) As the amount of LC756 added increases, the chromaticity coordinates move continuously from the long-wavelength region to the short-wavelength region along the visible light spectrum, and the change path is clear, indicating that it has good controllability in structural color regulation and stable optical performance.
[0050] To illustrate the temperature response of the structural color of the CLCE-LM composite film, a CLCE-LM composite film with 5% LC756 additive was used for DSC testing. Figure 15 The isotropic phase transition temperature of the thin film was measured. The initial temperature of the film was approximately 81°C, and its color was green. When the temperature exceeded this value... At that time, the original green structural color basically disappeared, and the film as a whole appeared dark gray. This may be due to the temperature rising above [a certain level]. Upon cooling to room temperature, the cholesteric helical structure inside the film is disrupted, and the structural color fades. After cooling, the helical structure is reconstructed by the cross-linking network, and the green structural color is restored. Figure 15 It exhibits good thermal response reversibility, which provides a foundation for its application in temperature visualization monitoring and thermal response optical devices.
[0051] To illustrate the mechanical properties of cholesteric liquid crystal elastomer-based liquid metal composite films, CLCE-LM composite films were prepared with an LC756 addition of 4%, an LM particle addition of 40 wt.%, and a particle size of approximately 315 nm. The stress-strain curves of the composite film and the pure CLCE film were then compared. Figure 16 In (a), the elongation at break is about 140%. After the introduction of LM particles, the overall ductility of the film is not affected and good stretchability is maintained. The fracture stress decreases slightly, which may be because the LM particles are dispersed in the elastomer matrix, which weakens the effective load-bearing capacity and stress transmission of the matrix, resulting in a slight decrease in fracture strength, but still has good mechanical properties.
[0052] The CLCE-LM composite film was subjected to 100 cycles of stretching under 40% strain conditions. Figure 16 (b) In the initial cycle, the film's resilience slightly decreased, exhibiting a minor stress softening phenomenon. This may be due to the rearrangement of the polymer network within the material during loading, the stretching and relaxation of some physical entanglements, and the release of micro-stress concentration at the interface between the LM particles and the matrix, resulting in irreversible microstructural adjustments in the initial stage. As the number of cycles increases, the internal structure of the material gradually stabilizes, and the variation amplitude of the cycle curves decreases significantly. The curves of the 10th and 100th cycles essentially overlap, indicating that the CLCE-LM composite film possesses good cyclic tensile stability and mechanical reliability during repeated deformation.
[0053] To illustrate the optical response of the composite film during strain, a film initially exhibiting a red color was subjected to uniaxial stretching. Figure 17 (a) As the tensile strain increases, the film color undergoes a continuous change from red to blue. At a strain of 60%, its color changes from red to blue, exhibiting good strain response sensitivity and translating mechanical deformation into intuitive visual feedback. This is because during stretching, the elastomer network elongates along the stretching direction, while the helical structure perpendicular to the stretching direction compresses, reducing the pitch P. According to Bragg's law of reflection, the wavelength of light selectively reflected by the CLCE shifts to shorter wavelengths, macroscopically manifesting as a change in structural color. Reflectance spectroscopy was then performed on it (…). Figure 17 (b) As the tensile strain increases, the wavelength of the maximum reflected light in the film gradually shifts to blue, consistent with the macroscopic color change, indicating that the CLCE-LM composite film has good stress sensing characteristics and has application value in the field of visual strain sensing.
[0054] The CLCE-LM composite film, initially red in color, was pressed upwards from the bottom using a circular probe. Figure 18 At pressures of 40 kPa, 80 kPa, and 160 kPa, the color of the film in the pressed area changed from red to yellow, green, and blue, respectively. This is because during the pressing process, the normal pressure compresses the helical axis, reducing the pitch and shifting the center wavelength of the selectively reflected light towards shorter wavelengths, resulting in a blue shift in the structural color and enabling a visual response to the pressure signal.
[0055] To illustrate the resistivity response of the composite film during strain, the resistivity change of the CLCE-LM film under different uniaxial tensile strains was measured. Figure 19 As the tensile deformation increases, the rate of change of film resistivity gradually increases overall. At a strain of 30%, the rate of change of resistivity is only about 6%, while at a strain of 60%, the rate of change of resistivity is about 24%. Because the LM particles form good conductive pathways in the CLCE matrix after sintering, the LM particles undergo synergistic deformation with the stretching of the matrix during the stretching process. During the stretch recovery process, the rate of change of resistivity is similar to that during the stretching process, indicating that it has good conductive stability.
[0056] To demonstrate the repeatability of the resistive response of the composite thin film, the rate of change of resistance of the CLCE-LM composite thin film under different strain cycles was tested. Figure 20 (a) The resistivity change rate of the film under different tensile strains exhibits good repeatability, and its tensile deformation can be reflected by the resistivity change rate. Under a strain of 20%, 100 cycles of tensile testing were performed. Figure 20 (b) The resistance change rate of the thin film is about 3%, and the resistance change rate remains basically unchanged after 100 cycles, indicating good resistance stability.
[0057] To illustrate the application of composite films in human motion monitoring, the film was fixed at the index finger joint, and the change rate of film resistance as a function of the finger bending angle was measured. Figure 21 (a) As the bending angle increases, the rate of change of film resistance gradually increases, reaching approximately 42% at a bending angle of 90°. Cyclic tests were conducted at finger bending angles of 30°, 45°, 60°, and 90°. Figure 21 (b) The resistance change rate at the same bending angle has good repeatability. As the bending angle increases, the thin film resistance change rate gradually increases, which can generate a resistance signal output for the amplitude of finger movement and has real-time monitoring capability.
[0058] In summary, the CLCE-LM composite film can convert stretching, pressing, and human joint movements into stable and recognizable electrical signals, exhibiting excellent response characteristics and cycle stability. It also possesses multimodal signal sensing characteristics with structural color response, providing a new design approach for constructing multimodal sensing smart materials that integrate visual perception and electrical signal acquisition. This offers broad application prospects in flexible electronic skin, intelligent wearable systems, and human-computer interaction.
[0059] Example 3: In this embodiment, the liquid metal composite film based on cholesteric phase liquid crystal elastomer is further assembled into a triboelectric nanogenerator. Its structure and working principle can be found in [reference needed]. Figure 22 The triboelectric nanogenerator includes an upper electrode and a lower electrode. The upper electrode is composed of a conductive tape (copper tape) and a polymer friction film, which can be a PE film or a PTFE film. The lower electrode is a liquid metal composite film based on a cholesteric liquid crystal elastomer, wherein the sparse regions of liquid metal particles serve as the friction contact regions, and the regions rich in liquid metal particles serve as the conductive electrode regions, thereby utilizing the layered structure of the composite film itself to achieve the integrated setting of the friction layer and the electrode layer.
[0060] The operation of the triboelectric nanogenerator includes four stages: initial contact, separation, maximum separation, and re-contact. In the initial contact stage, the upper polymer triboelectric film and the surface of the cholesteric liquid crystal elastomer-based liquid metal composite film are in full contact. Due to their different electronegativity, charge transfer occurs at the contact interface, forming equal amounts of opposite triboelectric charges. In the separation stage, the upper and lower triboelectric layers gradually separate. The residual triboelectric charges at the interface cannot be instantaneously neutralized, causing a change in the spatial charge distribution and creating a potential difference between the upper and lower electrodes. Electrons are transferred through the external circuit, generating an instantaneous voltage signal. In the maximum separation stage, the potential difference reaches its peak value. In the re-contact stage, the interfacial potential difference reverses, electrons flow in the opposite direction, generating a reverse voltage signal, thus completing one voltage output cycle.
[0061] To illustrate the effect of liquid metal particles on the output performance of triboelectric nanogenerators, the dielectric properties of CLCE thin films and CLCE-LM composite films were tested respectively. Figure 23The dielectric constants of both thin films gradually decreased with increasing frequency, with a significant decrease in the low-frequency region. This is mainly related to the response capabilities of dipole orientation polarization and interfacial polarization at different frequencies. The dielectric constant of the CLCE-LM composite film was higher than that of the CLCE film throughout the entire test frequency range, with the most significant decrease in the low-frequency band, indicating that the addition of LM particles enhanced the dielectric response capability of the film. This may be because, under the action of an applied electric field, a large number of microcapacitor structures are formed between the LM particles and the surrounding CLCE substrate, enhancing the interfacial polarization effect. Furthermore, the presence of an oxide layer on the surface of the LM particles can serve as a charge accumulation interface, further enhancing space charge polarization under low-frequency electric fields, thereby increasing the overall dielectric constant.
[0062] PTFE film was selected respectively ( Figure 24 a) and PE film ( Figure 24 In section b), the triboelectric properties of the TENG were tested using PTFE as the upper friction layer. When the upper friction layer was PTFE, the output voltage signal was approximately 0.8V. When PE was used instead, the output voltage was approximately 3.8V, and the signal remained stable. This is mainly due to the difference in electronegativity between PE and the CLCE-LM film. Compared to PTFE, PE and the CLCE-LM film accumulate more surface charge during the contact-separation process, resulting in a higher output voltage. By adjusting the type of material at the contact interface, the output voltage level of the TENG can be effectively adjusted, and the type of contact material can be distinguished.
[0063] Using PTFE as the upper friction layer, TENG was assembled and the relationship between its output voltage signal and contact frequency was tested. Figure 25 As the contact frequency decreases, the peak frequency of the output voltage signal decreases synchronously, showing a good correlation, which can be used for real-time monitoring of the motion cycle.
[0064] To illustrate the pressure detection capability, a finger was used as the contact layer of the TENG, and the voltage signal of the CLCE-LM composite film under different pressures was tested. Figure 26 Under repeated pressure, the voltage signal exhibits good repeatability. At 80 kPa, the output voltage is approximately 0.27 V, demonstrating good pressure sensitivity. As the pressure gradually increases, the voltage signal amplitude gradually strengthens. This may be due to the increased contact area between the finger and the film, enhanced interfacial charge separation of the LM particles during pressing, increased interfacial polarization, increased internal material deformation, and increased charge accumulation, leading to a higher output voltage amplitude. This demonstrates that the output voltage of the CLCE-LM composite film can respond regularly to changes in applied pressure within a certain range, exhibiting good amplitude adjustability and signal stability. It can effectively distinguish pressure, showing good application potential in flexible pressure sensing and multimodal sensing applications.
[0065] Example 4: Based on the above embodiments, an application of a liquid metal composite film in the fabrication of an optoelectronic dual-mode sensor is provided, characterized in that the liquid metal composite film is prepared by the liquid metal composite film preparation method in Example 1; In the optical-electric dual-mode sensor, the upper region of the composite film serves as a structural color response layer, used to generate structural color changes under external mechanical stimulation; the lower region of the composite film serves as a conductive functional layer, used to generate resistance change signals under the external mechanical stimulation. By acquiring the structural color change and the resistance change signals, optical visualization recognition and electrical quantitative detection of the external mechanical stimuli can be achieved.
[0066] The external mechanical stimulation includes at least one of stretching, pressing, and bending.
[0067] The structural color change is used to determine the location or deformation state of the external mechanical stimulus, and the resistance change signal is used to determine the intensity of the external mechanical stimulus.
[0068] The optical-electric dual-modal sensor is a strain sensor, pressure sensor, human joint motion sensor, flexible electronic skin, or smart wearable sensor.
[0069] The human joint motion sensor is used to detect finger bending movements, and the resistance change signal increases as the finger bending angle increases.
[0070] Therefore, the liquid metal composite film based on cholesteric liquid crystal elastomer prepared in this invention can not only achieve photoelectric dual-modal sensing of strain, pressure, and human joint movement through structural color changes and resistance changes, but also further construct triboelectric nanogenerators to achieve contact material identification, contact frequency monitoring, and pressure detection. This composite film integrates structural color visualization feedback, electrical signal output, and energy conversion functions through the functional division between the sparse region of the upper liquid metal particles and the rich region of the lower liquid metal particles, making it suitable for flexible electronic skin, smart wearable systems, intelligent interactive systems, and self-driven sensors.
[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a liquid metal composite thin film, characterized in that, Includes the following steps: S1. Liquid metal is added to a dispersion medium and ultrasonically dispersed to obtain a liquid metal suspension. The liquid metal suspension is centrifuged to obtain liquid metal particle precipitate. The liquid metal particle precipitate is added to deionized water for treatment to obtain liquid metal particles. S2. Dissolve liquid crystal monomers and chiral liquid crystal molecules in a solvent to form a liquid crystal mixed solution. Then add a catalyst, chain extender, crosslinking agent and photoinitiator to the liquid crystal mixed solution and mix them to obtain a liquid crystal precursor solution for forming a cholesteric phase liquid crystal elastomer matrix. S3. Add liquid metal particles to the liquid crystal precursor solution and disperse them to obtain a composite precursor solution containing liquid metal particles; S4. The composite precursor solution is placed in a film-forming mold and allowed to stand to allow the solvent to evaporate. During the solvent evaporation process, liquid crystal molecules are induced to self-assemble to form a cholesteric helical ordered structure and undergo Michael addition cross-linking. At the same time, liquid metal particles spontaneously settle in the composite precursor solution along the thickness direction to form a layered structure. The bottom region of the layered structure has a dense distribution of liquid metal particles, while the upper region has a relatively sparse distribution of liquid metal particles. S5. Photocuring the layered structure yields a liquid metal composite film based on cholesteric liquid crystal elastomer. In this process, the relatively sparse distribution of liquid metal particles corresponds to the formation of structural color response regions, while the dense distribution of liquid metal particles corresponds to the formation of conductive functional regions, enabling the liquid metal composite film based on cholesteric liquid crystal elastomer to generate structural color changes and electrical signal outputs under the action of external force.
2. The preparation method according to claim 1, characterized in that, In step S1, the dispersion medium is anhydrous ethanol, and the liquid metal is a gallium-indium alloy; The liquid metal particles are precipitated and treated by adding them to deionized water. This process includes adding the liquid metal particles precipitated to deionized water and dispersing them by vortexing, followed by rapid freezing with liquid nitrogen and vacuum freeze-drying to obtain liquid metal particles.
3. The preparation method according to claim 1, characterized in that, In step S2, the solvent is toluene. The liquid crystal monomer and the chiral liquid crystal molecule are dissolved in the toluene under heating conditions. After cooling, the catalyst, the chain extender, the thiol crosslinking agent and the photoinitiator are added.
4. The preparation method according to claim 3, characterized in that, In step S2, the liquid crystal monomer is RM257, the chiral liquid crystal molecule is LC756, the catalyst is DPA, the chain extender is EDDET, the thiol crosslinking agent is PETMP, and the photoinitiator is I-651.
5. The preparation method according to claim 1, characterized in that, The amount of liquid metal particles added to the composite precursor solution is from 35 wt.% to 60 wt.%.
6. The preparation method according to claim 1, characterized in that, The liquid metal particles have a particle size of 300 nm to 400 nm, and the amount of liquid metal particles added to the composite precursor solution is 40 wt.%.
7. The preparation method according to claim 4, characterized in that, The molar ratio of the liquid crystal monomer RM257, the chain extender EDDET, and the thiol crosslinking agent PETMP is 1.06:0.08:0.85, and the amount of photoinitiator I-651 added is 1 wt.%.
8. A liquid metal composite thin film, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 7.
9. A triboelectric nanogenerator, characterized in that, It includes an upper electrode and a lower electrode. The upper electrode includes a conductive tape and a polymer friction film disposed on one side of the conductive tape. The lower electrode is a liquid metal composite film based on cholesteric liquid crystal elastomer prepared by the preparation method according to any one of claims 1 to 7. The sparse region of the liquid metal particles faces the polymer friction film and serves as the friction contact area, while the rich region of the liquid metal particles serves as the conductive electrode area, enabling the triboelectric nanogenerator to output a voltage signal during the contact separation process.
10. The application of the liquid metal composite thin film as described in claim 8 in the fabrication of an opto-electronic dual-mode sensor, characterized in that, The upper region of the composite film serves as a structural color responsive layer, used to generate structural color changes under external mechanical stimulation; the lower region of the composite film serves as a conductive functional layer, used to generate resistance change signals under the external mechanical stimulation. By acquiring the structural color change and the resistance change signals, optical visualization recognition and electrical quantitative detection of the external mechanical stimuli can be achieved.